The Everyday Creativity of Authentic Classroom Assessments (LEARNing Landscapes, 2021)
This paper examines the everyday creativity embedded within authentic classroom assessments. While not all authentic assessments are necessarily creative (i.e., novel, innovative, and contextually appropriate), I demonstrate everyday creativity in two authentic classroom assessments I have adopted in my TESOL courses. In revealing the everyday creativity of these tasks, and in light of their desired learning outcomes, I seek to demystify the role everyday creativity can play in student demonstrations of knowledge and skill.
Keywords: everyday creativity; authentic assessments; TESOL